Video Games as Culture Considering the Role and Importance of Video Games in Contemporary Society - GARCÍA MARTÍN, Joseba (Revista Española de Investigaciones Sociológicas, 2024)
Es reseña de: Video Games as Culture. Considering the Role and Importance of Video Games in Contemporary Society Daniel Muriel, Garry Crawford Routledge, 2018